Analysis Of Healthcare-Associated Infections (HAIs) Surveillance System At RSUD Drs. H. Amri Tambunan Regional Hospital Deli serdang Regency: Analysis Of Healthcare-Associated Infections (HAIs) Surveillance System At Drs. H. Amri Tambunan Regional Hospital Deli serdang Regency - Sirait, Reni Aprinawaty; Arum Puspita Sari; Rotua Sumihar Sitorus (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Surveillance of Health Care Associated Infections (HAIs) is a dynamic and continuous process of collecting, identifying, analyzing, and interpreting health data. This study aims to analyze the HAIs surveillance system based on input, process, and output components using a mixed-method approach. Phase I (quantitative) assessed input (human resources and infrastructure) and output (epidemiological data and HAIs incidence rates) using secondary data analyzed univariately. Phase II (qualitative) explored input and process components through interviews and FGDs with the IPC team (IPCN and IPCLN), analyzed using thematic analysis. Results from Phase I showed the highest HAIs cases in patients over 41 years, with VAP incidence in February (32.5 ‰) exceeding the standard. Other peaks included non-SC IDO in February (1.58 ‰), SC IDO in April (5 ‰), and phlebitis in March (1.11 ‰). Phase II revealed issues in HR quality, incomplete SOPs, limited infrastructure, and lack of indicators to assess data completeness and accuracy